Epidemic activity of respiratory syncytial virus is related to temperature and rainfall in equatorial tropical countries (2020)
Although viral acute lower respiratory infections (ALRIs) are a major public health problem in tropical low- and middle-income countries (LMICs), and there is growing evidence showing their relationship with meteorological parameters, studies performed in these countries are scarce. In an analytical cross-sectional study, we determined which of the main meteorological parameters (temperature, absolute humidity, rainfall, wind speed, and solar radiation) predicted respiratory syncytial virus (RSV) activity in a population of hospitalized children with ALRI during a 5-year period, from January 2009 to December 2013. Out of a total of 4559 children included in the study (mean age 9·2 ± 8·5 months), 2953 (64·8%) presented RSV infection during the 3-month period from March to May. In the multivariate analysis, after controlling for absolute humidity, wind speed, and solar radiation, temperature [incidence rate ratio (IRR) 2·25, 95% confidence interval (CI) 1·11–4·53, P = 0·024], and rainfall (IRR 1·01, 95% CI 1·00–1·02, P = 0·044) were independently associated with the monthly number of RSV infections. In conclusion, in Bogota, the capital of a tropical LMIC lying slightly above the equator, RSV activity peaks in the 3-month period from March to May, the main rainy period of the year in the city. In addition, rainfall and temperature are the two most important meteorological parameters that are independently associated with RSV activity in hospitalized children with ALRI in the city.